2005
DOI: 10.1111/j.1475-1313.2005.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Refractive index and equilibrium water content of conventional and silicone hydrogel contact lenses

Abstract: New relationships are presented that correlate nominal and measured values of EWC and refractive index for the silicone containing hydrogels. The linear relationships derived fit well to the data. Hand refractometry overestimates the EWC of silicone hydrogel materials and this bias is related to the proportion of siloxane moieties in the material. Conversely, refractive index can be obtained more accurately with automated refractometry for silicone hydrogels than for conventional hydrogels. Present results are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 11 publications
4
45
0
Order By: Relevance
“…Conversely, the SCL shows the lower relative difference (3%), and as a high-water content hydrogel material, this will have the closest refractive index to that assumed for the cornea. 30,31 Nevertheless, this hypothesis of refractive index playing a significant role in accuracy of OCT measures of lens material thickness should be adequately addressed in other studies.…”
Section: Discussionmentioning
confidence: 97%
“…Conversely, the SCL shows the lower relative difference (3%), and as a high-water content hydrogel material, this will have the closest refractive index to that assumed for the cornea. 30,31 Nevertheless, this hypothesis of refractive index playing a significant role in accuracy of OCT measures of lens material thickness should be adequately addressed in other studies.…”
Section: Discussionmentioning
confidence: 97%
“…oxygen permeability) and optical properties like the refractive index [15,16]. More recently, Lord et al [17] also observed that when lysozyme and cholesterol solutions contact hydrogels of poly(2-hydroxyethylmethacrylate) and methacrylic acid (P(HEMA-MAA)), changes in the hydrogel structure occur, with water being displaced.…”
Section: Introductionmentioning
confidence: 95%
“…The CLR 12-70 automated lens refractometer (Index Instruments U.S., Inc., USA) provides direct estimates of the RI; however, the disadvantage is that it is expensive and has been used in only a few studies. 17,18 Spectroscopy too has the same limitations as the CLR 12-70. Refractometry using the Brix-based RI measure is an inexpensive, simple, indirect method based on the Gladstone-Dale law, which assumes a correlation of the RI to the water content of the material.…”
mentioning
confidence: 96%